Perioperative, Single-Surgeon Experience in Cerebrovascular Bypass Procedures at Academic Medical Center and Community Hospital - Nissman, Kathleen W.; Zomorodi, Ali R.; Gupta, Dhanesh K.; Dhakal, Ishwori; Li, Yi-Ju; James, Michael L. (Journal of Neuroanaesthesiology and Critical Care, 2018)
Background Little evidence exists for superiority of neurosurgical outcomes from care subspecialization. Outcomes of a single neurosurgeon after complex vascular neurosurgery in an academic medical center were compared against those in a community hospital.Methods In this retrospective analysis of extracranial-intracranial vascular bypass operations performed between July 1, 2013 and February 1, 2015, cases were identified by cross-referencing the electronic medical record with the surgeon's own records. Pre-, intra-, and postoperative variables were abstracted from cases performed at a tertiary center and a community hospital. Dichotomous postoperative data recorded included extubation in the operating room (OR), readmission, and survival to discharge, and length of stay was also analyzed. Due to small sample size and low readmission rate, Firth's penalized likelihood tests were incorporated in the logistic regression model for parameter estimation and testing.Results A total of 28 hemispheres in 26 patients were included: 18 hemispheres in 16 patients at the tertiary center and 10 hemispheres in 9 patients at the community hospital. Differences were found in operative time (tertiary mean: 7.21 + 2.5 hours, community mean: 5.19 + 0.9 hours, p = 0.0074) and readmission to the tertiary center (p = 0.078). However, significant difference was observed only for anesthetic type (more likely to include remifentanil and propofol at the tertiary center, p = 0.0104).Conclusion Subspecialty care alone may be insufficient to enhance outcome after complex neurosurgical procedures.
Keywords: moyamoya; extracranial intracranial bypass; subspecialty care; community hospital care; neuroanesthesiology; neurosurgery